Unlawful issuance of the “Guidelines on the Applicable Legal Provisions Regarding Access to the Procedure for Terminating a Pregnancy” - Gęsiak, Katarzyna (Finding a way out of Poland’s rule-of-law crisis: Possible courses of action and reform, 2026)
On August 30, 2024, then-Minister of Health Izabela Leszczyna issued "Guidelines on the Applicable Legal Provisions Regarding Access to Abortion Procedures," which were subsequently distributed to hospital directors and department heads. The Guidelines were accompanied by amendments to a regulation on general terms of healthcare contracts, introducing severe financial penalties against facilities that failed to comply with their content. This document, carrying no force of universally binding law, effectively created a new normative reality while bypassing the legislative process entirely. It enabled the performance of abortions without medical indications and without gestational limits — as illustrated, among other cases, by an incident in Oleśnica, where a physician terminated the life of a child in the ninth month of pregnancy. The Guidelines stand in obvious contradiction to the constitutional protection of human life. The Minister of Health should revoke the Guidelines without delay and inform physicians of their non-binding nature. The author also calls for an amendment to the regulation removing the unlawful financial penalty provisions, and — looking further ahead — for the introduction of systemic solutions that would prevent unconstitutional interpretations of laws protecting human life.